Use of Excel Software for Graphing for PAUD Luwu Timur Teachers: Penggunaan Perangkat Lunak Excel Untuk Pembuatan Grafik pada Guru PAUD di Luwu Timur - Rusli; Abdul Rahman; Hastuty; Sitti Masyitah Meliyana R.; Ranak Lince (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The training aims to provide insight, abilities, and skills of PAUD Luwu Timur teachers in graphing using excel software. The method used is to conduct lectures, practice, and discussions between teachers and the implementation team. The result of this training is that the teachers are skilled and proficient in using Microsoft excel features in drawing graphs or charts, including Bar charts, Scatter, Line charts, and Pie, the teachers are also pleased and interested in using the features possessed by Microsoft Excel.